MINDSET KEWIRAUSAHAAN BAGI SISWA SMA - Zubaidah Nasution; Agustinus Kismet Nugroho; Shinta Setia (-)
AbtractEquivalence education package C program is education that takes place outside the school system, but the competence of graduates is considered equivalent to the competency of formal education graduates. This program is for high school students in the city of Surabaya who dropped out of school due to social, economic, time, opportunity and geographic limitations who cannot concentrate in a busy school environment, as well as home schooling students. This procurement aims to provide assistance in starting an entrepreneur, providing supporting facilities to produce products and training in making online media and social media to market products. This activity is carried out twice as the first implementation, focused on making business proposals students are encouraged to make starting from the title, introduction (business background), marketing mix (product, price, promotion, place), SWOT analysis (strengths, weakness, opportunity, thread), calculation of budget costs, market potential and profits and documentation. In the implementation of the two PKBM students, a business proposal presentation competition and social media competition were held. In the percentage of business proposals and proposals, the criteria for evaluating PKBM percentages and business proposals consist of business percentages, creativity, preparation of budget calculations, program potential: market opportunities and potential profitability. In social media evaluation, PKBM social media evaluation criteria consist of the most likes on social media on instagram and the best caption.